A short-process high-strength, low-pinhole, heat-resistant power battery aluminum foil and its preparation method

By optimizing the Fe/Si ratio and adding microalloy elements, combined with composite spiral electromagnetic stirring and pulse current-assisted rolling process, the problem of insufficient strength and heat resistance of the power battery aluminum foil is solved, and high strength, low pinhole rate, and heat resistance of aluminum foil is achieved, which improves battery performance and production efficiency.

CN119101831BActive Publication Date: 2025-03-07NANJING INST OF TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411238962.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-03-07
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The aluminum foil of existing power batteries has complex process and high energy consumption, resulting in poor strength, toughness and heat resistance, affecting the energy density and service life of the battery.

Method used

By optimizing the Fe/Si ratio, adding Y, Er, and Sc microalloy elements, and using composite spiral electromagnetic stirring process and pulse current assisted rolling process, the pinhole rate of the aluminum foil is reduced and its strength and toughness are improved.

Benefits of technology

Aluminum foil with high strength, low pinhole rate and heat resistance is achieved, which improves the energy density and service life of the battery, while reducing production costs and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119101831B_ABST
    Figure CN119101831B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-strength, low-pinhole rate, heat-resistant power battery aluminum foil produced by a short process and a preparation method thereof, belonging to the technical field of power battery materials and processing methods. A high-strength, low-pinhole rate, heat-resistant power battery aluminum foil produced by a short process includes the following components: Fe: 0.21-0.55%; Si: 0.15-0.35%; Cu: 0.02-0.08%; Ti: 0.01-0.04%; Mn≤0.02%; Zn≤0.02%; Y: 0.003-0.005%; Er: 0.003-0.005%; Sc: 0.003-0.005%; the rest is Al. In the smelting stage, the present invention improves the uniformity of the melt and the effects of alkali removal, impurity removal and degassing through composite spiral electromagnetic stirring; introduces a new rolling method assisted by pulse current, increases the degree of grain refinement, and greatly improves production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-strength, low-pinhole rate, heat-resistant power battery aluminum foil produced by a short process and a preparation method thereof, belonging to the technical field of power battery materials and processing methods. Background Art

[0002] In order to alleviate the increasingly severe energy form and energy conservation and emission reduction pressure, the replacement of traditional fuel vehicles by new energy vehicles is an inevitable development trend in the transportation industry. The rapidly growing market demand for new energy emerging industries has put forward higher requirements for the performance of high energy density and long life battery power batteries. Aluminum foil current collector is an important component of power batteries, which plays the role of loading electrode active materials, converging current and conducting it. High electrode compaction density is conducive to improving the energy density of power batteries, thereby obtaining long-term performance. This requires the aluminum foil current collector to have high strength, toughness, low pinhole rate and other characteristics to ensure that it is not easy to break the belt, defects and other problems in the battery production coating and rolling process.

[0003] At present, the aluminum foil of power batteries is mainly made of 1060 alloy, and the finished product is usually made by processes such as "casting + multi-pass cold rolling + homogenization annealing + foil rolling". The process is relatively complex and energy-intensive, which limits the improvement of production efficiency. In addition, the comprehensive mechanical properties of the aluminum foil, such as tensile strength and elongation, are low (tensile strength 200MPa, elongation less than 3%), and the pinhole rate is high, which greatly affects the yield of high-performance power batteries and increases production costs. In addition, the mechanical properties of the aluminum foil current collector decay at high temperatures, which will cause the active material to fall off, shorten the battery life and cause safety problems.

[0004] Therefore, it is necessary to provide a high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process and a preparation method thereof to solve the above problems. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a high-strength, low-pinhole rate, and heat-resistant power battery aluminum foil produced by a short process, by optimizing the Fe / Si ratio and regulating a variety of micro-alloy components, designing a composite spiral electromagnetic stirring process, and optimizing the pulse current assisted rolling process, a uniform and fine grain structure is obtained, and the quality defects such as pinholes and holes on the surface of the aluminum foil are greatly reduced. By increasing the single deformation amount of aluminum foil rolling, reducing the rolling and annealing process steps, greatly improving production efficiency, reducing production time and cost, and obtaining a low pinhole rate, high strength, high toughness, and heat-resistant power battery aluminum foil, the energy density and service life of new energy power batteries can be effectively improved.

[0006] At the same time, the present invention provides a high-strength, low-pinhole rate, heat-resistant power battery aluminum foil produced by a short process.

[0007] At the same time, the present invention provides a high-strength, low-pinhole rate, heat-resistant power battery aluminum foil produced by a short process for use in new energy vehicles.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0009] A high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process, comprising the following components, measured by mass percentage: Fe: 0.21-0.55%; Si: 0.15-0.35%; Cu: 0.02-0.08%; Ti: 0.01-0.04%; Mn≤0.02%; Zn≤0.02%; Y: 0.003-0.005%; Er: 0.003-0.005%; Sc: 0.003-0.005%; and the rest is Al.

[0010] Preferably, the composition of the power battery aluminum foil is controlled to have a mass fraction ratio of ω(Fe) / ω(Si) of (1.2-1.5): 1. This is to avoid the appearance of a coarse needle-shaped second phase, and to improve the alloy plasticity by combining the grain refinement and second phase refinement effects of Y, Er, and Sc elements, facilitating subsequent rolling processing.

[0011] A method for preparing a high-strength, low-pinhole, and heat-resistant power battery aluminum foil produced by a short process comprises the following steps:

[0012] Step 1, smelting and refining: adding an aluminum ingot to a smelting furnace, and when the aluminum is hydrated, adding 80FeAl, AlSi20, Al-Cu, Al-Ti, Al-Mn, and Al-Zn according to the above-mentioned composition ratio to continue smelting, the smelting temperature is 750-760°C, the smelting time is 3-5h, and then the melt is fully stirred by a composite spiral electromagnetic stirring method, that is, an alternating current is loaded in the circumferential and vertical directions of the melt, and at the same time, a ceramic rotor is arranged at the bottom of the furnace to blow argon gas for refining and slagging, the refining temperature is 750-760°C, and the time is 1-2h; then, a sodium-free particle refining agent is blown into the furnace with argon gas, and the refining is continued for at least 30min, and the amount of the sodium-free particle refining agent is 1-2kg·t Al;

[0013] Then, the melt is introduced into a static furnace, and Al-Y, Al-Er, and Al-Sc refining agents are blown into the melt according to the above-mentioned composition ratio by argon blowing, and the refining is continued for at least 30 minutes. After refining, the melt is allowed to stand and the slag is removed;

[0014] Step 2, degassing and filtering: The aluminum alloy melt refined in step 1 is introduced into a degassing box for online degassing. After treatment, the hydrogen content of the aluminum alloy melt is less than 0.1mL / 100g Al, the diameter of the aluminum slag is less than 0.005mm, and the slag content is less than 0.1mm 2 / kg;

[0015] Step 3, casting and rolling: after 1 to 3 passes of casting and rolling into 3 to 7 mm billets, a cast-rolled plate is obtained;

[0016] Step 4, pulse current assisted rolling: placing the cast-rolled slab in a semi-enclosed protective cover of a pulse current assisted device, introducing argon gas, and performing two pulse current assisted rolling, wherein the pulse current is introduced perpendicular to the direction of the cast-rolled slab, wherein the rolling force of the first rolling is 300-500t, the roll temperature is between 100-300°C, the deformation is between 40%-50%, and the thickness of the aluminum coil after rolling is between 2-3mm, and the rolling force of the second rolling is 200-400t, the roll temperature is between 200-400°C, the deformation is between 30%-40%, and the thickness of the aluminum coil after rolling is between 0.2-0.3mm, to obtain a semi-finished product;

[0017] Step 5, foil rolling: the semi-finished product obtained in step 4 is foil rolled to a finished product of 0.012-0.02 mm through 2-3 passes, with a rolling force of 300-400 t, a rolling speed of 600-1200 mm / min, and an oil temperature of 40-60°C;

[0018] Step six: finished products are cut, annealed, packaged and stored.

[0019] Preferably, the sodium-free particle refining agent includes KF+K3AlF6, KF+KAIF4 or KF+K3AlF6+KAIF4 series.

[0020] Preferably, in step 1, the ceramic rotor speed is 400-650 r / min, the gas pressure is 0.3-0.6 MPa, and the flow rate is 0.3-0.5 m 3 / h.

[0021] Preferably, in step one, the composite spiral electromagnetic stirring method is: three-phase low-frequency alternating current, the phase angle of the alternating current passed through the circumferentially distributed convex-type iron core differs by 60 to 120°, and the current with the same phase is loaded in the relative coil; the phase angle of the vertically equidistantly distributed traveling wave coil differs by 30 to 90°, and the current with the same phase is loaded in the interval coil; the stirring frequency is 1 to 12 Hz, the output current is 100 to 250A, and the stirring time is 30 to 80 minutes. This step optimizes the phase angle, frequency, current and time of the circumferential and vertical square alternating current, so that the melt moves in multiple angles and directions, fully stirs evenly, further improves the melt removal and degassing effect, ensures the purity of the melt, and prevents the quality defects of the aluminum foil caused by impurities and pinholes.

[0022] Preferably, in step 2, the degassing and filtering method is: introduce the aluminum alloy melt refined in step 1 into a degassing box for online degassing, using argon as the degassing medium, with a flow rate of 5 to 15 L / min, and the degassing box temperature is 720±10°C, and then undergoes three-stage filtration to remove impurities, the filter plate is a 40PPi+60PPi double-stage filtration ceramic foam filter plate, and an RB grade 7 tubular filtration device.

[0023] Preferably, in step three, the casting and rolling process is: the front box casting nozzle adopts a three-stage diverter block, the front box liquid level height is 40±1mm, the front box temperature is 700±5℃, the casting and rolling gap is 0.3~0.5mm, the casting and rolling speed is 800~1000mm / min, the casting and rolling zone length is controlled at 55~65mm, the roller surface temperature is 70~90℃, and the rolling force is 200~800t.

[0024] Preferably, in step 4, the loading pulse electrical parameters are voltage 10-50V, electrical pulse frequency 200-800Hz, pulse width 10-500μs, and duty cycle 5%-20%. By optimizing the pulse electrical parameters and rolling force, controlling the rolling temperature and deformation, the deformation activation energy of the aluminum rolled plate is minimized, the degree of grain refinement during the rolling process is increased, and the internal stress of the rolled plate is reduced, which is convenient for the subsequent foil rolling process.

[0025] A high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process is used in new energy vehicles.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] (1) The present invention optimizes the Fe / Si content ratio in the melt, adds Al-Y, Al-Er, Al-Sc multi-component modifiers and strictly controls the content, changes the morphology of iron-rich and silicon-rich impurity phases, and synergistically refines the billet grains and the second phase structure. The Al3Y, Y5Si3, Al3Er, and Al3Sc strengthening phases formed with the microalloying elements Y, Er, and Sc ensure the comprehensive properties of the aluminum foil, such as high strength, low pinhole rate, and heat resistance.

[0028] (2) The present invention uses a composite spiral electromagnetic stirring process to control the strength and direction of the circumferential and vertical magnetic fields, thereby achieving stirring at different angles and intensities, improving the melt stirring effect, and using composite stirring and cavitation effects to form a local supercooling zone in the melt, promoting the precipitation of Fe and Si element impurities, increasing the number of new crystal nuclei, refining the grains, and preventing the formation of coarse needle-shaped iron-rich phases in the alloy. At the same time, the interdependence of inclusions and gases in the aluminum melt is reduced, further improving the melt uniformity and the alkali removal, impurity removal and degassing effects, improving the alloy plasticity, reducing the surface porosity and defects of the billet during the rolling process, and ensuring product stability.

[0029] (3) The present invention optimizes the pulse electrical parameters and rolling process through a new rolling method assisted by pulse current, which can reduce the deformation activation energy of aluminum rolled plate and increase the single deformation amount of aluminum foil rolling. Combined with the control of the Fe / Si content ratio and the Y / Er / Sc element content in the melt, and the composite spiral stirring process to ensure the cleanliness of the melt, the coarse dendrites are transformed into fine and uniform grains, the strengthening phase is dispersedly distributed, and the recrystallization nucleation rate and grain refinement degree are increased. By strictly controlling the rolling temperature and deformation amount, reducing the rolling passes, annealing and other process steps, the production cycle can be shortened by more than 35%, the energy consumption can be reduced by more than 35%, and the production efficiency can be greatly improved. It can also significantly improve the mechanical properties and heat resistance of the material, and obtain a high-strength, low-pinhole, and heat-resistant power battery aluminum foil.

[0030] The preparation method of the present invention comprises the following steps: smelting and refining, degassing and filtering, casting and rolling, pulse current assisted rolling, foil rolling, finished product slitting, annealing, packaging and warehousing. Compared with the prior art, the present invention reduces the aggregation of large-sized impurities by optimizing the Fe / Si ratio and regulating a variety of microalloy components, and obtains a uniform and fine grain structure; the composite spiral electromagnetic stirring process is designed to improve the melt uniformity and the effect of impurity removal and degassing, and greatly reduce the quality defects such as pinholes and holes on the surface of the aluminum foil. By loading the rolling method of pulse current, the single deformation amount of aluminum foil rolling is increased, and the rolling and annealing process steps are reduced, which not only greatly improves the production efficiency, but also obtains a power battery aluminum foil with excellent comprehensive properties such as high strength, low pinhole rate, and heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a surface morphology image of the aluminum foil prepared in Example 2 of the present invention;

[0032] Figure 2 This is the microstructure diagram of the aluminum foil blank prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0033] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0034] Example 1

[0035] A high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process, including the following components: Fe: 0.21%; Si: 0.15%; Cu: 0.02%; Ti: 0.01%; Mn: 0.01%; Zn: 0.01%; Y: 0.003%; Er: 0.003%; Sc: 0.003%; the rest is Al.

[0036] The preparation method comprises the following steps:

[0037] (1) Melting and refining: Add aluminum ingots to the melting furnace. When the aluminum is hydrated, add 80FeAl, AlSi20, Al-Cu, Al-Ti, Al-Mn, and Al-Zn according to the above-mentioned composition ratio and continue melting. Control ω(Fe) / ω(Si) to 1.4, the melting temperature to 750℃, and the melting time to 3h. Then, the melt is fully stirred by a composite spiral electromagnetic stirring method, and a three-phase low-frequency alternating current is applied to the melt in the circumferential and vertical directions. The phase angle of the alternating current applied to the circumferentially distributed convex-type iron core differs by 60°, and the current with the same phase is applied to the relative coils; the phase angle of the vertically equidistantly distributed traveling wave coils differs by 30°, and the interval coils are loaded with the same phase current. The stirring frequency is 1Hz, the output current is 100A, and the stirring time is 30min. At the same time, the ceramic rotor is arranged at the bottom of the furnace to blow argon for refining and slagging. The refining temperature is 750℃, the time is 1h, the ceramic rotor speed is 400r / min, the gas pressure is 0.3Mpa, and the flow rate is 0.3m 3 / h; then use argon to blow KF+K3AlF6 type sodium-free granular refining agent (the mass ratio of KF and K3AlF6 is 1:1) into the furnace and continue refining for 30 minutes. The amount of refining agent is 1kg·t Al. Introduce into the static furnace, and use argon blowing to blow Al-Y, Al-Er, and Al-Sc refining agents into the melt according to the composition ratio and continue refining for 30 minutes. After refining, let it stand and remove the slag.

[0038] (2) Degassing and filtering: The aluminum melt refined in step (1) is introduced into a degassing box for online degassing, using argon as the degassing medium, with a flow rate of 5 L / min and a degassing box temperature of 720°C. It is then filtered and impurities are removed by three stages, with the filter plate being a 40PPi+60PPi double-stage filter ceramic foam filter plate and an RB-level 7-tube filter device. After treatment, the hydrogen content of the aluminum alloy melt is less than 0.1 ml / 100 g Al, the aluminum slag diameter is less than 0.005 mm, and the slag content is less than 0.1 mm 2 / kg.

[0039] (3) Casting and rolling: The front box casting nozzle adopts a three-level diverter block, the front box liquid level height is 40 mm, the front box temperature is 700℃, the casting and rolling gap is 0.3 mm, the casting and rolling speed is 800 mm / min, the casting and rolling zone length is controlled at 55 mm, the roller surface temperature is 70℃, the rolling force is 800t, and after three passes of casting and rolling, a 7 mm billet is formed.

[0040] (4) Pulse current assisted rolling: The cast slab is placed in a semi-enclosed protective cover of a pulse current assisted device, argon gas is introduced, and two pulse current assisted rolling is performed. The pulse current is introduced perpendicular to the rolling direction of the plate. The loading pulse electrical parameters are voltage 10V, electric pulse frequency 200Hz, pulse width 10μs, and duty cycle 5%. Among them, the first rolling force is 300t, the roll temperature is 300℃, the deformation is between 40% and 45%, and the thickness of the aluminum coil after rolling is between 2.5 and 3mm. The second rolling force is 400t, the roll temperature is 200℃, the deformation is between 30% and 35%, and the thickness is between 0.25 and 0.3mm.

[0041] (5) Foil rolling: The semi-finished product obtained in step (4) is subjected to three passes of foil rolling to a finished product of 0.012 mm, with a rolling force of 400 t, a rolling speed of 600 mm / min, and an oil temperature of 40°C.

[0042] (6) Finished products are cut, annealed, packaged and stored.

[0043] A high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process is used in new energy vehicles.

[0044] The average grain size of the aluminum billet prepared in this embodiment is 58 μm. The thickness of the aluminum foil prepared in this embodiment is 12 μm, the tensile strength is 260 MPa, the elongation is 4.0%, and the pinhole rate is 10 / m 2 When the aluminum foil was kept at 200° C. for 30 min, its tensile strength was 235 MPa and its elongation was 3.7%, which still had relatively excellent mechanical properties, indicating that the aluminum foil prepared in this example had good heat resistance.

[0045] Example 2

[0046] A high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process, including the following components: Fe: 0.35%; Si: 0.30%; Cu: 0.04%; Ti: 0.04%; Mn: 0.02%; Zn: 0.02%; Y: 0.004%; Er: 0.004%; Sc: 0.004%; the rest is Al.

[0047] The preparation method comprises the following steps:

[0048] (1) Melting and refining: Add aluminum ingots to the melting furnace. When the aluminum is hydrated, add 80FeAl, AlSi20, Al-Cu, Al-Ti, Al-Mn, and Al-Zn according to the above-mentioned composition ratio and continue melting. Control ω(Fe) / ω(Si) to 1.2, the melting temperature to 755℃, and the melting time to 4h. Then, the melt is fully stirred by a composite spiral electromagnetic stirring method, and a three-phase low-frequency alternating current is applied to the melt in the circumferential and vertical directions. The phase angle of the alternating current applied to the circumferentially distributed convex-type iron core differs by 90°, and the current with the same phase is applied to the relative coils; the phase angle of the vertically equidistantly distributed traveling wave coils differs by 60°, and the interval coils are loaded with the same phase current. The stirring frequency is 8Hz, the output current is 200A, and the stirring time is 50min. At the same time, the ceramic rotor is arranged at the bottom of the furnace to blow argon for refining and slagging. The refining temperature is 755℃, the time is 1h, the ceramic rotor speed is 550r / min, the gas pressure is 0.6Mpa, and the flow rate is 0.5m 3 / h; then use argon to blow KF+K3AlF6+KAlF4 series sodium-free granular refining agent (the mass ratio of KF, K3AlF6 and KAlF4 is 1:1:1) into the furnace and continue refining for 30 minutes. The amount of refining agent is 1.5kg·t Al. Introduce into the static furnace, and blow Al-Y, Al-Er, and Al-Sc refining agents into the melt according to the composition ratio by argon blowing, and continue refining for 30 minutes. After refining, let it stand and remove slag.

[0049] (2) Degassing and filtering: The aluminum melt refined in step (1) is introduced into a degassing box for online degassing, using argon as the degassing medium, with a flow rate of 15 L / min and a degassing box temperature of 720°C. It is then filtered and impurities are removed in three stages, with the filter plate being a 40PPi+60PPi double-stage filter ceramic foam filter plate and an RB-level 7-tube filter device. After treatment, the hydrogen content of the aluminum alloy melt is less than 0.1 ml / 100 g Al, the aluminum slag diameter is less than 0.005 mm, and the slag content is less than 0.1 mm 2 / kg.

[0050] (3) Casting and rolling: The front box casting nozzle adopts a three-level diverter block, the front box liquid level height is 40.5 mm, the front box temperature is 705°C, the casting and rolling gap is 0.4 mm, the casting and rolling speed is 1000 mm / min, the casting and rolling zone length is controlled at 60 mm, the roller surface temperature is 80°C, the rolling force is 700t, and after two passes of casting and rolling, a 5 mm billet is formed.

[0051] (4) Pulse current assisted rolling: The cast slab is placed in a semi-enclosed protective cover of a pulse current assisted device, argon gas is introduced, and two pulse current assisted rolling is performed. The pulse current is introduced perpendicular to the rolling direction of the plate. The loading pulse electrical parameters are voltage 20V, electric pulse frequency 500Hz, pulse width 200μs, and duty cycle 10%. Among them, the rolling force of the first rolling is 400t, the roll temperature is 200℃, the deformation is between 45% and 50%, and the thickness of the aluminum coil after rolling is between 2 and 3mm. The rolling force of the second rolling is 300t, the roll temperature is 300℃, the deformation is between 35% and 40%, and the thickness is between 0.2 and 0.3mm.

[0052] (5) Foil rolling: The semi-finished product obtained in step (4) is subjected to two passes of foil rolling to a finished product of 0.02 mm, with a rolling force of 350 t, a rolling speed of 800 mm / min, and an oil temperature of 55°C.

[0053] (6) Finished products are cut, annealed, packaged and stored.

[0054] A high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process is used in new energy vehicles.

[0055] The average grain size of the aluminum billet prepared in this embodiment is 43 μm. The thickness of the aluminum foil prepared in this embodiment is 20 μm, the tensile strength is 275 MPa, the elongation is 4.5%, and the pinhole rate is 6 / m 2 When the aluminum foil is kept at 200°C for 30 minutes, its tensile strength is 254MPa and its elongation is 4.1%. Its mechanical properties are still 90% higher than those at room temperature.

[0056] Example 3

[0057] A high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process, including the following components: Fe: 0.55%; Si: 0.35%; Cu: 0.08%; Ti: 0.01%; Mn: 0.02%; Zn: 0.02%; Y: 0.005%; Er: 0.003%; Sc: 0.005%; the rest is Al.

[0058] The preparation method comprises the following steps:

[0059] (1) Melting and refining: Add aluminum ingots to the melting furnace. When the aluminum is hydrated, add 80FeAl, AlSi20, Al-Cu, Al-Ti, Al-Mn, and Al-Zn according to the above-mentioned composition ratio and continue melting. Control ω(Fe) / ω(Si) to 1.5, the melting temperature to 760℃, and the melting time to 5h. Then, the melt is fully stirred by a composite spiral electromagnetic stirring method, and a three-phase low-frequency alternating current is applied to the melt in the circumferential and vertical directions. The phase angle of the alternating current applied to the circumferentially distributed convex-type iron core differs by 120°, and the current with the same phase is applied to the relative coils; the phase angle of the vertically equidistantly distributed traveling wave coils differs by 90°, and the current with the same phase is applied to the interval coils. The stirring frequency is 12Hz, the output current is 250A, and the stirring time is 80min. At the same time, the ceramic rotor is arranged at the bottom of the furnace to blow argon for refining and slagging. The refining temperature is 760℃, the time is 2h, the ceramic rotor speed is 650r / min, the gas pressure is 0.3Mpa, and the flow rate is 0.5m 3 / h; then use argon to blow KF+KAlF4 series sodium-free granular refining agent (the mass ratio of KF and KAlF4 is 1:1) into the furnace and continue refining for 40 minutes. The amount of refining agent is 2kg·t Al. Introduce into the static furnace, and blow Al-Y, Al-Er, and Al-Sc refining agents into the melt according to the composition ratio by argon blowing, and continue refining for 40 minutes. After refining, let it stand and remove slag.

[0060] (2) Degassing and filtering: The aluminum melt refined in step (1) is introduced into a degassing box for online degassing, using argon as the degassing medium, with a flow rate of 15 L / min and a degassing box temperature of 710°C. It is then filtered and impurities are removed in three stages, with the filter plate being a 40PPi+60PPi double-stage filter ceramic foam filter plate and an RB grade 7 tubular filter device. After treatment, the hydrogen content of the aluminum alloy melt is less than 0.1 ml / 100 g Al, the aluminum slag diameter is less than 0.005 mm, and the slag content is less than 0.1 mm 2 / kg.

[0061] (3) The front box casting nozzle adopts a three-level diverter block, the front box liquid level height is 41 mm, the front box temperature is 695 ° C, the casting and rolling gap is 0.5 mm, the casting and rolling speed is 1000 mm / min, the casting and rolling zone length is controlled at 65 mm, the roller surface temperature is 90 ° C, the rolling force is 200 t, and after one pass, the billet is cast and rolled into 3 mm.

[0062] (4) Pulse current assisted rolling: The cast slab is placed in a semi-enclosed protective cover of a pulse current assisted device, argon gas is introduced, and two pulse current assisted rolling is performed. The pulse current is introduced perpendicular to the rolling direction of the plate. The loading pulse electrical parameters are voltage 50V, electric pulse frequency 800Hz, pulse width 500μs, and duty cycle 20%. Among them, the rolling force of the first rolling is 500t, the roll temperature is 100℃, the deformation is between 45% and 50%, and the thickness of the aluminum coil after rolling is between 2.0 and 2.5mm. The rolling force of the second rolling is 200t, the roll temperature is 400℃, the deformation is between 35% and 40%, and the thickness is between 0.2 and 0.25mm.

[0063] (5) Foil rolling: The semi-finished product obtained in step (4) is subjected to three passes of foil rolling to a finished product of 0.012 mm, with a rolling force of 300 t, a rolling speed of 1200 mm / min, and an oil temperature of 60°C.

[0064] (6) Finished products are cut, annealed, packaged and stored.

[0065] A high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process is used in new energy vehicles.

[0066] The average grain size of the aluminum billet prepared in this embodiment is 67 μm, the thickness of the aluminum foil prepared in this embodiment is 12 μm, the tensile strength is 258 MPa, the elongation is 3.3%, and the pinhole rate is 15 / m 2 When the aluminum foil is kept at 200°C for 30 minutes, its tensile strength is 231 MPa and its elongation is 2.9%.

[0067] Comparative Example 1

[0068] A power battery aluminum foil, the alloy has the following composition: Fe: 0.2%; Si: 0.25%; Cu: 0.03%; Ti: 0.01%; Mn: 0.01%; Zn: 0.01%; the rest is Al. The remaining production steps are in accordance with Example 1 to obtain a power battery aluminum foil, wherein the average grain size of the aluminum billet after casting is 83 μm, the tensile strength of the aluminum foil is 208 MPa, the elongation is 2.1%, and the pinhole rate is 63 pieces / m 2 , the aluminum foil was kept at 200°C for 30 minutes, and its tensile strength was 142MPa and its elongation was 2.0%. Compared with Example 1, the Fe / Si ratio was not strictly controlled and Y, Sc, and Er microalloying elements were not added, resulting in a large number of coarse needle-like AlFeSi phases in the structure, an increase in the number of pinholes in the aluminum foil, and coarse grains, lacking the second phase strengthening effect of microalloying elements, and low mechanical properties at room temperature and high temperature.

[0069] Comparative Example 2

[0070] A power battery aluminum foil comprises the following components: Fe: 0.35%; Si: 0.30%; Cu: 0.04%; Ti: 0.04%; Mn: 0.02%; Zn: 0.02%; Y: 0.004%; Er: 0.004%; Sc: 0.004%; and the rest is Al.

[0071] The preparation method comprises the following steps:

[0072] (1) Melting and refining: Add aluminum ingots to the melting furnace. When the aluminum is hydrated, add 80FeAl, AlSi20, Al-Cu, Al-Ti, Al-Mn and Al-Zn according to the above-mentioned composition ratio and continue to melt. Control ω(Fe) / ω(Si) to 1.2, the melting temperature to 755°C, the melting time to 4h, and stir evenly. At the same time, arrange a ceramic rotor at the bottom of the furnace to blow argon for refining and slagging. The refining temperature is 755°C, the time is 1h, the ceramic rotor speed is 550r / min, the gas pressure is 0.6Mpa, and the flow rate is 0.5m 3 / h; then use argon to blow KF+K3AlF6+KAlF4 series sodium-free granular refining agent into the furnace and continue refining for 30 minutes. The amount of refining agent is 1.5kg·t Al. Introduce into the static furnace, and use argon to blow Al-Y, Al-Er, and Al-Sc refining agents into the melt according to the composition ratio and continue refining for 30 minutes. After refining, let it stand and remove the slag.

[0073] (2) Degassing and filtering: The aluminum melt refined in step (1) is introduced into a degassing box for online degassing, using argon as the degassing medium, with a flow rate of 15 L / min and a degassing box temperature of 720°C. It is then filtered and impurities are removed in three stages, with the filter plate being a 40PPi+60PPi double-stage filter ceramic foam filter plate and an RB-level 7-tube filter device. After treatment, the hydrogen content of the aluminum alloy melt is less than 0.1 ml / 100 g Al, the aluminum slag diameter is less than 0.005 mm, and the slag content is less than 0.1 mm 2 / kg.

[0074] (3) Casting and rolling: The front box casting nozzle adopts a three-level diverter block, the front box liquid level height is 40.5 mm, the front box temperature is 705°C, the casting and rolling gap is 0.4 mm, the casting and rolling speed is 1000 mm / min, the casting and rolling zone length is controlled at 60 mm, the roller surface temperature is 80°C, the rolling force is 700t, and after two passes of casting and rolling, a 5 mm billet is formed.

[0075] (4) Pulse current assisted rolling: The cast slab is placed in a semi-enclosed protective cover of a pulse current assisted device, argon gas is introduced, and two pulse current assisted rolling is performed. The pulse current is introduced perpendicular to the rolling direction of the plate. The loading pulse electrical parameters are voltage 20V, electric pulse frequency 500Hz, pulse width 200μs, and duty cycle 10%. Among them, the rolling force of the first rolling is 400t, the roll temperature is 200℃, the deformation is between 45% and 50%, and the thickness of the aluminum coil after rolling is between 2 and 3mm. The rolling force of the second rolling is 300t, the roll temperature is 300℃, the deformation is between 35% and 40%, and the thickness is between 0.2 and 0.3mm.

[0076] (5) Foil rolling: The semi-finished product obtained in step (4) is subjected to two passes of foil rolling to a finished product of 0.02 mm, with a rolling force of 350 t, a rolling speed of 800 mm / min, and an oil temperature of 55°C.

[0077] (6) Finished products are cut, annealed, packaged and stored.

[0078] The aluminum billet prepared in this comparative example has an average grain size of 74 μm, a tensile strength of 225 MPa, an elongation of 2.3%, and a pinhole rate of 55 pcs / m 2 When the aluminum foil is kept at 200°C for 30 minutes, its tensile strength is 159 MPa and its elongation is 2.1%.

[0079] Compared with Example 2, this comparative example lacks the composite spiral electromagnetic stirring process in the smelting and refining steps, which reduces the uniformity of the melt, and impurities such as inclusions, alkali, and gas in the melt are not easy to eliminate, resulting in coarse grains of the billet and a high pinhole rate, which reduces the mechanical properties of the aluminum foil and the product stability.

[0080] Comparative Example 3

[0081] A power battery aluminum foil comprises the following components: Fe: 0.55%; Si: 0.35%; Cu: 0.08%; Ti: 0.01%; Mn: 0.02%; Zn: 0.02%; Y: 0.005%; Er: 0.003%; Sc: 0.005%; and the rest is Al.

[0082] The preparation method comprises the following steps:

[0083] (1) Melting and refining: Add aluminum ingots to the melting furnace. When the aluminum is hydrated, add 80FeAl, AlSi20, Al-Cu, Al-Ti, Al-Mn, and Al-Zn according to the above-mentioned composition ratio and continue melting. Control ω(Fe) / ω(Si) to 1.5, the melting temperature to 760℃, and the melting time to 3h. Then, the melt is fully stirred by a composite spiral electromagnetic stirring method, and a three-phase low-frequency alternating current is applied to the melt in the circumferential and vertical directions. The phase angle of the alternating current applied to the circumferentially distributed convex-type iron core differs by 120°, and the current with the same phase is applied to the relative coils; the phase angle of the vertically equidistantly distributed traveling wave coils differs by 90°, and the current with the same phase is applied to the interval coils. The stirring frequency is 12Hz, the output current is 250A, and the stirring time is 80min. At the same time, the ceramic rotor is arranged at the bottom of the furnace to blow argon for refining and slagging. The refining temperature is 760℃, the time is 2h, the ceramic rotor speed is 650r / min, the gas pressure is 0.3Mpa, and the flow rate is 0.5m3 / h. Then, the KF+KAlF4 series of sodium-free granular refining agents are blown into the furnace with argon and the refining continues for 30min. The refining agent dosage is 2kg·t Al. It is introduced into the static furnace, and the Al-Y, Al-Er, and Al-Sc refining agents are blown into the melt according to the composition ratio by argon blowing to continue refining for 30min. After refining, it is allowed to stand and slag is removed.

[0084] (2) Degassing and filtration: The aluminum melt refined in step (1) is introduced into a degassing box for online degassing, using argon as the degassing medium with a flow rate of 15 L / min and a degassing box temperature of 720°C. It is then filtered and impurities are removed by three stages, using a 40PPi+60PPi double-stage filtration ceramic foam filter plate and a RB-level 7-tube filter device. After treatment, the hydrogen content of the aluminum alloy melt is less than 0.1 ml / 100 g Al, the aluminum slag diameter is less than 0.005 mm, and the slag content is less than 0.1 mm2 / kg.

[0085] (3) Casting and rolling: The front box casting nozzle adopts a three-level diverter block, the front box liquid level height is 41 mm, the front box temperature is 705°C, the casting and rolling gap is 0.5 mm, the casting and rolling speed is 1000 mm / min, the casting and rolling zone length is controlled at 65 mm, the roller surface temperature is 90°C, the rolling force is 200t, and after one pass of casting and rolling, a 3 mm billet is formed.

[0086] (4) Cold rolling: After casting and rolling, the billet undergoes six passes of cold rolling and homogenization annealing to obtain the subsequent foil-rolled semi-finished product.

[0087] (5) Foil rolling: The semi-finished product obtained in step (4) is subjected to three passes of foil rolling to a finished product of 0.012 mm, with a rolling force of 300 t, a rolling speed of 1200 mm / min, and an oil temperature of 60°C.

[0088] (6) Finished products are cut, annealed, packaged and stored.

[0089] The aluminum billet prepared in this comparative example has an average grain size of 71 μm, a tensile strength of 223 MPa, an elongation of 2.5%, and a pinhole rate of 36 pcs / m 2 When the aluminum foil is kept at 200°C for 30 minutes, its tensile strength is 173 MPa and its elongation is 2.4%.

[0090] Compared with Example 3, this comparative example lacks the pulse current assisted rolling process after casting and rolling, and adopts the traditional multi-pass cold rolling and homogenization annealing process, which not only increases the production process steps, prolongs the cycle, and reduces the product output efficiency, but also lacks the large deformation of the pulse current assisted rolling process, reduces the recrystallization nucleation rate and grain refinement degree, and limits the improvement of mechanical properties.

[0091] from Figure 1 It can be seen that the surface of the aluminum foil prepared by the method of Example 2 is smooth and has almost no pinholes. Figure 2 It can be seen that the grain size is small and uniform, no coarse needle-like structure appears, and the strengthening phase is fine and dispersed. It can be seen from Table 1 that the power battery aluminum foil prepared according to Examples 1, 2, and 3 of the present invention has a relatively small and uniform grain size compared with the aluminum foil prepared in the comparative example, and the tensile strength and elongation of the aluminum foil are significantly improved, and the pinhole rate is low. The present invention controls the Fe / Si content ratio and adds Y / Er / Sc micro-content modifiers to eliminate coarse needle-like structures and refine the grains; in the smelting stage, the melt uniformity and the alkali removal, impurity removal and degassing effects are improved by composite spiral electromagnetic stirring; the introduction of a new rolling method assisted by pulse current increases the degree of grain refinement and greatly improves production efficiency. The aluminum foil prepared in Comparative Examples 1, 2, and 3 has low mechanical properties at room temperature and high pinhole rates, and the mechanical properties are severely attenuated at high temperatures. The tensile strength and elongation of the aluminum foil prepared in Examples 1, 2, and 3 at a high temperature of 200°C can reach more than 90% of the results at room temperature, and are still higher than the tensile strength and elongation of the corresponding comparative examples, indicating that the present invention produces high-strength, low-pinhole rate, and heat-resistant power battery aluminum foil through a short process.

[0092] Table 1 Performance test results of Examples 1, 2, 3 and Comparative Examples 1, 2, 3

[0093]

[0094] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.

[0095] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.

[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process, characterized in that: In terms of mass percentage, it includes the following components: Fe: 0.21~0.55%; Si: 0.15~0.35%; Cu: 0.02~0.08%; Ti: 0.01~0.04%; Mn≤0.02%; Zn≤0.02%; Y: 0.003~0.005%; Er: 0.003~0.005%; Sc: 0.003~0.005%; the rest is Al; The preparation method comprises the following steps: Step 1, smelting and refining: adding aluminum ingots to a smelting furnace, and when the aluminum is hydrated, adding 80FeAl, AlSi20, Al-Cu, Al-Ti, Al-Mn, and Al-Zn according to the above-mentioned composition ratio to continue smelting, the smelting temperature is 750-760°C, the smelting time is 3-5h, and then the melt is fully stirred by a composite spiral electromagnetic stirring method, that is, alternating current is loaded in the circumferential and vertical directions of the melt, and argon is blown in combination with a ceramic rotor arranged at the bottom of the furnace for refining and slagging, the refining temperature is 750-760°C, and the time is 1-2h; then, a sodium-free particle refining agent is blown into the furnace with argon gas, and the refining is continued for at least 30min, and the amount of the sodium-free particle refining agent is 1-2kg·t Al; Then, the melt is introduced into a static furnace, and Al-Y, Al-Er, and Al-Sc refining agents are blown into the melt according to the above-mentioned composition ratio by argon blowing, and the refining is continued for at least 30 minutes. After refining, the melt is allowed to stand and the slag is removed; Step 2, degassing and filtering: The aluminum alloy melt refined in step 1 is introduced into a degassing box for online degassing. After treatment, the hydrogen content of the aluminum alloy melt is less than 0.1mL / 100g Al, the diameter of the aluminum slag is less than 0.005mm, and the slag content is less than 0.1mm 2 / kg; Step 3: Casting and rolling: After 1 to 3 passes of casting and rolling into 3 to 7 mm billets, cast-rolled plates are obtained; Step 4, pulse current assisted rolling: placing the cast-rolled slab in a semi-enclosed protective cover of a pulse current assisted device, introducing argon gas, and performing two pulse current assisted rolling, wherein the pulse current is introduced perpendicular to the direction of the cast-rolled slab, wherein the rolling force of the first rolling is 300-500t, the roll temperature is between 100-300°C, the deformation is between 40%-50%, and the thickness of the aluminum coil after rolling is between 2-3mm, and the rolling force of the second rolling is 200-400t, the roll temperature is between 200-400°C, the deformation is between 30%-40%, and the thickness of the aluminum coil after rolling is between 0.2-0.3mm, to obtain a semi-finished product; Step 5, foil rolling: the semi-finished product obtained in step 4 is foil rolled to a finished product of 0.012-0.02 mm for 2-3 passes, with a rolling force of 300-400 t, a rolling speed of 600-1200 mm / min, and an oil temperature of 40-60°C; Step six: finished products are cut, annealed, packaged and stored.

2. The method for preparing a high-toughness, low-pinhole rate, heat-resistant power battery aluminum foil produced by a short process according to claim 1, characterized in that: The controlled mass fraction ratio of the components of power battery aluminum foil is: ω (Fe) / ω (Si) is (1.2~1.5):

1.

3. The preparation method according to claim 1, characterized in that: Sodium-free granular refining agents include KF+K3AlF6, KF+KAlF4 or KF+K3AlF6+KAlF4 series.

4. The preparation method according to claim 1, characterized in that: In step 1, the ceramic rotor speed is 400~650r / min, the gas pressure is 0.3~0.6 MPa, and the flow rate is 0.3~0.5m 3 / h.

5. The preparation method according to claim 1, characterized in that: In step one, the composite spiral electromagnetic stirring method is: three-phase low-frequency alternating current, the phase angle of the alternating current passed through the circumferentially distributed convex-step iron core differs by 60~120°, and the current with the same phase is loaded in the relative coil; the phase angle of the vertically equidistantly distributed traveling wave coil differs by 30~90°, and the interval coil is loaded with the current with the same phase; the stirring frequency is 1~12Hz, the output current is 100~250A, and the stirring time is 30~80min.

6. The preparation method according to claim 1, characterized in that: In step 2, the degassing and filtering method is: the aluminum alloy melt refined in step 1 is introduced into a degassing box for online degassing, argon is used as the degassing medium, the flow rate is 5~15L / min, the degassing box temperature is 720±10℃, and then it is filtered and impurities are removed through three stages, the filter plate is a 40PPi+60PPi double-stage filtration ceramic foam filter plate, and an RB grade 7 tubular filter device.

7. The preparation method according to claim 1, characterized in that: In step three, the casting and rolling process is as follows: the front box casting nozzle adopts a three-stage diverter block, the front box liquid level height is 40±1mm, the front box temperature is 700±5℃, the casting and rolling gap is 0.3~0.5mm, the casting and rolling speed is 800~1000mm / min, the casting and rolling zone length is controlled at 55~65mm, the roller surface temperature is 70~90℃, and the rolling force is 200~800t.

8. The preparation method according to claim 1, characterized in that: In step 4, the loading pulse electrical parameters are voltage 10~50V, electric pulse frequency 200~800Hz, pulse width 10~500μs, and duty cycle 5%~20%.

9. Application of a high-strength, low-pinhole, heat-resistant power battery aluminum foil produced by a short process according to the preparation method according to any one of claims 1 to 8 in new energy vehicles.

Citation Information

Patent Citations

  • Production process for preparing double-zero-foil aluminum foil by utilizing electrolytic aluminum liquid

    CN118109709A